A first chironomid-based summer temperature reconstruction (13–5 ka BP) around 49°N in inland Europe compared with local lake development. (1st June 2016) - Hájková, Petra; Pařil, Petr; Petr, Libor; Chattová, Barbora; Matys Grygar, Tomáš; Heiri, Oliver
Abstract: Temperature reconstructions for the end of the Pleistocene and the first half of the Holocene based on biotic proxies are rare for inland Europe around 49°N. We analysed a 7 m long sequence of lake deposits in the Vihorlat Mts in eastern Slovakia (820 m a.s.l.). Chironomid head capsules were used to reconstruct mean July temperature (TJuly ), other proxies (diatoms, green algae, pollen, geochemistry) were used to reconstruct local environmental changes that might have affected the climate reconstruction, such as epilimnetic total phosphorus concentrations (TP), lake level changes and development of surrounding vegetation. During the Younger Dryas (YD), temperature fluctuated between 7 and 11 °C, with distinct, decadal to centennial scale variations, that agree with other palaeoclimate records in Europe such as δ 18 O content in stalagmites or Greenland ice cores. The results indicate that the site was somewhat colder than expected from the general south-to-north YD temperature gradient within Europe, possibly because of north-facing exposition. The warmer phases of the YD were characterised by low water level or even complete desiccation of the lake (12, 200–12, 400 cal yr BP). At the Late-Glacial/Holocene transition TJuly steeply increased from from 11 to 15.5 °C (11, 700–11, 400 cal yr BP) – the highest TJuly for entire sequence. This rapid climate change was reflected by all proxies as a compositional change and increasing species diversity. The open woodlands of Pinus, Betula, Larix and Picea were replaced by broad-leaved temperate forests dominated by Betula, later by Ulmus and finally by Corylus (ca 9700 cal yr BP). At the same time, input of eroded coarse-grained material into the lake decreased and organic matter (LOI) and biogenic silica increased. The Early-Holocene climate was rather stable till 8700 cal yr BP, with temporary decrease in TJuly around 11, 200 cal yr BP. The lake was productive with a well-developed littoral, as indicated by both diatoms and chironomids. A distinct decline of TJuly to 10 °C between 8700 and 8000 cal yr BP was associated with decreasing chironomid diversity and increasing climate moistening indicated by pollen. Tychoplanktonic and phosphorus-demanding diatoms increased which might be explained by hydrological and land-cover changes. Later, a gradual warming started after 7000 cal yr BP and representation of macrophytes, periphytic diatoms and littoral chironomids increased. Our results suggest that the Holocene thermal maximum was taking place unusually early in the Holocene at our study site, but its timing might be affected by topography and mesoclimate. We further demonstrated that temperature changes had coincided with variations in local hydrology. Highlights: Mean July temperature was reconstructed based on chironomids in East–Central Europe. Younger Dryas fluctuations coincided with changes in water level. All proxies mirrored rapid climate change at the Pleistocene-Holocene transition. Distinct thermal maximum started 11, 400 cal BP ago, followed by cooling since 8700 BP Algal, pollen and chemical proxies supported the chironomid-based climate reconstruction.